2021
DOI: 10.3390/nano11092174
|View full text |Cite
|
Sign up to set email alerts
|

Assembled Au/ZnO Nano-Urchins for SERS Sensing of the Pesticide Thiram

Abstract: In this paper, we are relating a significant improvement of the SERS effect achieved with assembled Au/ZnO nano-urchins. This improvement is realized thanks to an excellent capacity of adsorption (denoted K) for thiram molecules on these plasmonic nano-urchins, which is a key point to be taken into account for obtaining a SERS spectrum. Moreover, this outlook may be employed for different types of plasmonic substrates and for a wide number of molecules. We studied the capacity of the assembled Au/ZnO nano-urch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Currently, it is widely used in agricultural products such as fruits and vegetables as a fungicide . However, excessive use of thiram in agricultural products may cause diseases and other health problems in humans and livestock because of its strong enrichment effect . Therefore, the detection of thiram residues on the irregular surface of agricultural products is of great practical importance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is widely used in agricultural products such as fruits and vegetables as a fungicide . However, excessive use of thiram in agricultural products may cause diseases and other health problems in humans and livestock because of its strong enrichment effect . Therefore, the detection of thiram residues on the irregular surface of agricultural products is of great practical importance.…”
Section: Resultsmentioning
confidence: 99%
“…55 However, excessive use of thiram in agricultural products may cause diseases and other health problems in humans and livestock because of its strong enrichment effect. 56 Therefore, the detection of thiram residues on the irregular surface of agricultural products is of great practical importance. To realize the practical applications of as-fabricated flexible M-Ag@BNC SERS sensors, the Raman signals of thiram solutions with different concentrations collected on M-Ag-12@BNC paper are detected by a simple and feasible paste-and-read method on an irregular orange surface.…”
Section: Resultsmentioning
confidence: 99%
“…While the toxicity of most fungicides is generally low, prolonged exposure to these compounds may lead to adverse health effects such as neurological disruptions 126 . Several recent studies have utilized SERS to detect various fungicides, including tetramethylthiuram disulfide (THR), 39,53,61,70,79,127–161 carbendazim, 162–165 chlorothalonil, 166,167 MG, 168–173 TBZ (a fungicide and parasiticide) 20,79,153,155,173–178 and ferbam 20,178,179 . Among them, THR is the most studied due to its wide agricultural applications and strong binding with SERS nanosubstrates through the thiol group.…”
Section: Analytes Of Interestmentioning
confidence: 99%
“…Although excellent SERS performance was achieved, the facile fabrication of ZnO films with good uniformity and enhanced SERS activity, followed by a systematic investigation of the mechanism of the facet–dependent SERS enhancement from the view of the electronic work function is highly desirable. 40,41 Herein, three facet–defined ({101̄0}, {0001} and {101̄1}) ZnO films were successfully prepared and directly employed as substrates to investigate the facet–dependent SERS performance. Both the experimental and calculation results revealed that ZnO exposed with {101̄1} facets exhibits the strongest SERS enhancement and lowest LOD.…”
Section: Introductionmentioning
confidence: 99%